A Possible Novel Protective Effect of Piceatannol against Isoproterenol (ISO)-Induced Histopathological, Histochemical, and Immunohistochemical Changes in Male Wistar Rats - Samar A. Alghamdi; Maryam H. Mugri; Nahid M. H. Elamin; Mona Awad Kamil; Hind Osman; Basma G. Eid; Rasheed A. Shaik; Soad S. Shaker; Aziza Alrafiah (Current Issues in Molecular Biology, 2022)
Dry mouth is characterized by lower saliva production and changes in saliva composition. In patients with some salivary gland function remaining, pharmaceutical treatments are not recommended; therefore, new, more effective methods of promoting saliva production are needed. Hence, this study aimed to provide an overview of the histological changes in the salivary gland in the model of isoproterenol (ISO)-induced degenerative changes in male Wistar rats and to evaluate the protective effect of piceatannol. Thirty-two male Wistar rats were randomly divided into four groups: the control group, the ISO group, and the piceatannol (PIC)-1, and -2 groups. After the third day of the experiment, Iso (0.8 mg/100 g) was injected intraperitoneally (IP) twice daily into the animals. PIC was given IP in different daily doses (20 and 40 mg/kg) for three days before ISO and seven days with ISO injection. The salivary glands were rapidly dissected and processed for histological, histochemical, immunohistochemical (Ki-67), and morphometric analysis. Upon seven days of treatment with ISO, marked hypertrophy was observed, along with an increased number of positive Ki-67 cells. Proliferation was increased in some endothelial cells as well as in ducts themselves. Despite the significant decrease in proliferation activity, the control group did not return to the usual activity level after treatment with low-dose PIC. Treatment with a high dose of PIC reduced proliferative activity to the point where it was substantially identical to the results seen in the control group. An ISO-driven xerostomia model showed a novel protective effect of piceatannol. A new era of regenerative medicine is dawning around PIC’s promising role.